DIPG-31. Prognostic and predictive biomarkers of response in children and young adults with H3K27M-altered diffuse intrinsic pontine glioma: results from a multi-center, interventional clinical trial (PNOC003). (3rd June 2022) - Kline, Cassie; Jain, Payal; Kilburn, Lindsay; Bonner, Erin; Gupta, Nalin; Crawford, John; Banerjee, Anu; Packer, Roger; Villanueva-Meyer, Javier; Luks, Tracy; Zhang, Yalan; Kambhampati, Madhuri; et al.
Abstract: BACKGROUND: Diffuse intrinsic pontine glioma (DIPG) is a fatal brain tumor. Herein, we report on novel prognostic and predictive genomic biomarkers identified in PNOC003, a multi-center precision medicine trial for children and young adults diagnosed with DIPG. METHODS: Patients aged 3-25 years were enrolled on PNOC003 based on radiographic diagnosis of DIPG. Pre-treatment tumor biopsies were analyzed using tumor-normal whole-exome sequencing and mRNA-tumor sequencing to determine biology-informed, multi-agent therapy following radiation therapy (RT). Whole-genome sequencing was performed as an exploratory study aim. Genomic biomarkers were investigated to identify predictors of RT response and overall survival (OS) in patients with confirmed H3K27M-altered DIPG. Prognostic biomarkers were verified in a retrospective, H3K27M-altered diffuse midline glioma cohort (n=22) from the Children's Brain Tumor Network (CBTN). RESULTS: Thirty patients enrolled on PNOC003 met molecular criteria for H3K27M-altered DIPG. TP53 was the most frequently altered driver gene (73%). Somatic alterations in PTEN > TP53 > PDGFRA were independently associated with OS ( P <0.05, in order of negative impact on survival). TP53 mutations associated with worse OS ( TP53 mut 11.1 mo [95% CI 8.7, 14]; TP53 wt 13.3 mo [95% CI 11.8, NA]; P =3e-2), chromosomal instability ( P =3e-3), and resistance to RT ( P =6e-4). Moreover, loss of chromosome 10q, encoding tumor suppressor PTEN, was associated with worse OS, co-occurred with PTEN alterations, biallelic PTEN inactivation and loss of gene expression. The combination of TP53 alterations and loss of 10q/ PTEN in H3K27M-altered DIPG was associated with the worst OS in a combined PNOC003 and CBTN cohort ( TP53 mut/10qdel, n=14, OS 8.4 mo [95% CI 7.4, 15.8]; TP53 mut/10qwt, n=20, OS 13.1 mo [95% CI 10.1, 17.2]; TP53 wt/10qwt, n=14, OS 15.5 mo [11.8, 29.4]; P =2e-3). CONCLUSION: PNOC003, a tissue-driven clinical trial, provided insights into prognostic and predictive genomic biomarkers and informed a novel molecular tumor classification system for H3K27M-altered DIPGs.